2014
DOI: 10.4028/www.scientific.net/amr.926-930.3364
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm Optimization of Shape Setup Calculation in Hot Strip Mill

Abstract: This paper has researched traditional algorithms. The defects had been pointed out and proved. According to this, setup calculation algorithm was optimized. Considering strip transverse flow and creep deformation, natural output profile was defined. Practical applications in domestic 1500 hot strip mill show that the setup calculation strategy achieved good effect and enhanced the profile and flatness precision

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Liu [11] compares and analyses the hot rolling mathematical models of various western companies, and found that there is still lacking optimization allocation model in the strategic models of real production plants. Liu et al [12] and Hao et al [13] conduct the parameter optimization on the multi-variable system of profile control model according to finite element analysis. However, it still adopts traditional models on allocation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [11] compares and analyses the hot rolling mathematical models of various western companies, and found that there is still lacking optimization allocation model in the strategic models of real production plants. Liu et al [12] and Hao et al [13] conduct the parameter optimization on the multi-variable system of profile control model according to finite element analysis. However, it still adopts traditional models on allocation strategies.…”
Section: Introductionmentioning
confidence: 99%